2010
DOI: 10.1007/s10620-010-1386-z
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Renal Response to Mycophenolate Mofetil and CNI Taper Promotes Survival in Liver Transplant Patients with CNI-Related Renal Dysfunction

Abstract: Sustained renal response to MMF and CNI dose reduction promotes long-term survival in liver transplant patients with CNI-induced renal dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…These observed differences in renal function between each group were not unexpected, particularly as acute renal failure is common directly after LT, and GFR has been shown to decrease and then stabilize at around nine months after transplantation . For patients in Groups C and D, the change in GFR mirrored the results observed in several clinical trials, where improvements in renal function have occurred following introduction of MMF and a marked reduction in doses of CNIs . The greatest improvement in renal function was observed for Group D, where a change of +11.1 mL/min/1.73 m 2 was noted at 12 months.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These observed differences in renal function between each group were not unexpected, particularly as acute renal failure is common directly after LT, and GFR has been shown to decrease and then stabilize at around nine months after transplantation . For patients in Groups C and D, the change in GFR mirrored the results observed in several clinical trials, where improvements in renal function have occurred following introduction of MMF and a marked reduction in doses of CNIs . The greatest improvement in renal function was observed for Group D, where a change of +11.1 mL/min/1.73 m 2 was noted at 12 months.…”
Section: Discussionsupporting
confidence: 59%
“…Mycophenolate mofetil (MMF) is a frequent constituent of low toxicity, CNI‐sparing immunosuppressive regimens. Several studies have demonstrated that MMF does not cause nephrotoxicity and can improve renal function in patients following LT, concomitant with a reduction in CNI . Data from controlled clinical trials or registries indicate that MMF may benefit patients following LT with respect to renal function and by reducing metabolic abnormalities .…”
mentioning
confidence: 99%
“…Long‐term follow‐up data over 60 months from a study by Kornberg et al . demonstrated sustained renal response after conversion to reduced CNI and MMF therapy .…”
Section: Strategies For Avoiding/improving Chronic Renal Dysfunctionmentioning
confidence: 99%
“…There was significant improvement in eGFR over a 1 year follow-up period in the MMF and low dose CNI arm, without episodes of rejection. Furthermore, two other observational studies demonstrated significant GFR increases with conversion from standard CNI to reduced-dose CNI + MMF without adverse events (67, 70). The main benefit of this CNI reduction strategy was seen in applying this regimen within 1–2 years of LT.…”
Section: Key Points and Recommendationsmentioning
confidence: 92%
“…Renal protection late (>12 months) after LT Despite evidence of using mTOR-Is and MMF early after LT to minimize CNI nephrotoxicity, this strategy does not seem to apply as well later after LT (62)(63)(64)(65)(66)(67)(68)(69) (62). There was significant improvement in eGFR over a 1-year follow-up period in the MMF and low-dose CNI arm, without episodes of rejection.…”
Section: Key Points and Recommendationsmentioning
confidence: 99%